The twilight of the Goths : the rise and fall of the Kingdom of Toledo, c. 565-711 - Livermore, H. V., 1914-2010 (Intellect, 2006)
Toledo, former capital of Spain until 1560, is now one of the most monumental of Spanish cities. In Roman times, it was originally a modest tribal township, which was eventually elevated to a national capital by the Visigoths (one of two main branches of the Goths, who along with their cousins, the Ostrogoths in South Russia, were considered barbarians across Europe).